2003
DOI: 10.1074/jbc.m307216200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Epithelial Na+ Channel by Cytosolic ATP

Abstract: The epithelial Na ؉ channel (ENaC), composed of three subunits (␣␤␥), is expressed in various Na ؉ -absorbing epithelia and plays a critical role in salt and water balance and in the regulation of blood pressure. By using patch clamp techniques, we have examined the effect of cytosolic ATP on the activity of the rat ␣␤␥ENaC (rENaC) stably expressed in NIH-3T3 cells and in MadinDarby canine kidney epithelial cells. The inward wholecell current attributable to rENaC activity ran down when these cells were dialyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
(62 reference statements)
1
14
0
Order By: Relevance
“…The amplified cDNAs were gel-purified, and cloned into a SmaI site of pBluescript II SK(+) (Stratagene). We sequenced both strands of two clones (#11, 17), and their sequences were confirmed to be identical to AkFaNaC. The EcoRI-XbaI fragments of the clones (#11, 17) were blunted, and cloned into the EcoRV site of pSD64TR, a modified vector originating from pSP64 (Promega, USA), to make pSD64TR-AkFaNaC.…”
Section: Molecular Cloningmentioning
confidence: 99%
“…The amplified cDNAs were gel-purified, and cloned into a SmaI site of pBluescript II SK(+) (Stratagene). We sequenced both strands of two clones (#11, 17), and their sequences were confirmed to be identical to AkFaNaC. The EcoRI-XbaI fragments of the clones (#11, 17) were blunted, and cloned into the EcoRV site of pSD64TR, a modified vector originating from pSP64 (Promega, USA), to make pSD64TR-AkFaNaC.…”
Section: Molecular Cloningmentioning
confidence: 99%
“…In this report (102), we have indicated that run-down of ENaC activity (NP o ) to 50% of its initial activity (NP o ) occurs 5 min after making excised outside-out patches with no (0 mM) cytosolic ATP, while cytosolic ATP of 2 mM almost completely maintains ENaC activity (NP o ) at its initial value with little run-down of ENaC activity in a hydrolysisindependent mechanism at least within 5 min after making excised outside-out patches. This report (102) also provides further evidence that ATP binds to aENaC and determines ATP binding site of aENaC. Further, ATP is required for non-genomic action of aldosterone on ENaC activity (NP o ) (103).…”
Section: Action Of Cytosolic Atp On Enac Activitymentioning
confidence: 82%
“…In addition to this information (48), we have reported that ATP itself directly acts on ENaC by measuring the activity of ENaC (NP o ) existing in excised outside-out patches (102). In this report (102), we have indicated that run-down of ENaC activity (NP o ) to 50% of its initial activity (NP o ) occurs 5 min after making excised outside-out patches with no (0 mM) cytosolic ATP, while cytosolic ATP of 2 mM almost completely maintains ENaC activity (NP o ) at its initial value with little run-down of ENaC activity in a hydrolysisindependent mechanism at least within 5 min after making excised outside-out patches.…”
Section: Action Of Cytosolic Atp On Enac Activitymentioning
confidence: 99%
“…Figure 5 shows that CFTR-gCl was still normally deactivated after K ϩ substitution with Na ϩ , even after removing Ca 2ϩ . (9,10,12,15,36,38). Even though such coordination is essential to maintaining the functional integrity of the cell in the face of changing rates of transepithelial salt transport, very little is known about the molecular mechanisms involved in this vital process.…”
Section: Methodsmentioning
confidence: 99%
“…Several physiological strategies have been reported to be involved in this process, such as 1) metabolic coupling in which availability of ATP is linked to cystic fibrosis transmembrane conductance regulator (CFTR; see Refs. 1 and 20) and epithelial Na ϩ channel (ENaC) activity in the apical membrane (15) and K ϩ recycling in the basolateral membrane (36), 2) cross talk between Na ϩ channels in the apical membrane and K ϩ channels in the basolateral membrane (9,12), and 3) permissive control of Ca 2ϩ -dependent activation of multiple Na ϩ transport pathways by intracellular Cl Ϫ (29). Recent evidence also suggests that cytosolic changes in Na ϩ and Cl Ϫ concentrations could control apical salt transport by regulating ENaC channels (8,10).…”
mentioning
confidence: 99%